Research of analog resonances in NSC KIPT - Vodin, A.N. (Вопросы атомной науки и техники, 2003)
The review of the results received at research of isobar-analog resonances in NSC KIPT in 1967-2002 is carried out. The basic accent is made on the data received at studying of g-decay of analog resonances in nuclei of 1d2s-shell. The questions connected with М1 transitions between analog and antianalog states, core polarization states, Е1 and l-forbidden М1 transitions with DT = 1, compound-compound transitions and constants of isospin interaction are considered.